Pengaruh Suhu dan Tekanan Vakum Terhadap Penguapan Air, Kekerasan dan Kerenyahan Keripik Buah Selama Proses Penggorengan - ., Jamaluddin; ., Suardy; Laga, Suriana (Teknik Mesin "TEKNOLOGI", 2011)
Hard and crunchy textures are specific properties of fried product prefered by consummers. To have hard and crunchy textures being appropriate with consummer taste, it is necessary to pay attantion the raw material and the changes occurred during frying process. The objective of this research is to study the effect of temperature and pressure on the texture of fruit chips during vacuum frying process. The samples are jack fruits fried at temperature of 90 and 100OC, with frying duration of 15-16 minutes at vacuum pressure of 10 and 15 kPa. All water in products is assumed to be free water causing texture change if the water is removed. The observed parameters are hardness, crunchiness, water content, temperature, and vacuum pressure. The research result showed that temperature and vacuum pressure affected hardness, cruchiness and water vaporization of product during frying. The changing rates of hardness and crunchiness were affected by vaporizing rate of free water according to water content in product. The model of hardness and crunchiness changes as a fuction of water vaporization could be used to predict changes of hardness and crunchiness of product during vacuum frying process. Keywords: temperature, pressure, water content, hardness and crunchiness